Electric Vehicle Charging Station Incentive Design for Low Utilization, Fast and Ultra-Fast Chargers in Indonesia - Daniel Prahara Eka Ramadhani; Utomo Sarjono Putro (Eduvest - Journal of Universal Studies, 2026)
This study addresses the financial feasibility challenges of deploying fast and ultra-fast electric vehicle charging station incentive design for low utilization, fast and ultra-fast chargers in Indonesia (EVCS) in Indonesia, where low utilization rates (<30%) create significant economic barriers. It evaluates the impact of government incentive schemes on investment viability using Discounted Cash Flow (DCF) simulations. Schemes analyzed include baseline (no incentive), CAPEX incentive, tariff incentive, and performance-based incentive (PBI), with key indicators: Net Present Value (NPV), IRR, and Payback Period. Simulations reflect utilization below 30%, typical outside major urban centres. Without incentives, projects show negative NPV and sub-threshold IRR. CAPEX incentives reduce upfront costs, improving feasibility; tariff incentives boost cash flow. PBIs, which provide fiscal support per kWh sold or utilization level, enhance sustainability by tying aid to usage. Sensitivity analysis confirms IRR sensitivity to utilization and CAPEX. The study concludes that combining capital and output-based incentives is essential to bridge the viability gap, especially in low-demand regions. This will accelerate EVCS deployment, bolster investor confidence, and advance national electrification goals via inclusive infrastructure.